2019
DOI: 10.21203/rs.2.19034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haemosporidioses in wild Eurasian blackbirds (Turdus merula) and song thrushes (T. philomelos): an in situ hybridization study with emphasis on exo-erythrocytic parasite burden

Abstract: Background Passerine birds are frequently infected with diverse haemosporidian parasites. While infections are traditionally considered benign in wild birds, recent studies demonstrated mortalities of passerine species due to exo-erythrocytic development of the parasites, which can damage organs in affected hosts. However, exo-erythrocytic development remains insufficiently investigated for most haemosporidian species and thus little is known about the virulence of tissue stages in wild passerine birds. The ai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Phanerozoites of P. giovannolai develop almost exclusively in the spleen of canaries but were never seen in the brain, whereas those of P. matutinum are found in numerous organs [ 1 ]. A comprehensive study on haemosporidioses of T. merula and T. philomelos confirmed that phanerozoites of P. matutinum pLINN1 develop in multiple organs [ 86 ], but tissue stages of pLINN1 were not yet studied in canaries. Additional experimental infections of canaries with pLINN1 could help confirm differences between P. giovannolai and P. matutinum pLINN1 regarding the location of tissue stage formation.…”
Section: Discussionmentioning
confidence: 99%
“…Phanerozoites of P. giovannolai develop almost exclusively in the spleen of canaries but were never seen in the brain, whereas those of P. matutinum are found in numerous organs [ 1 ]. A comprehensive study on haemosporidioses of T. merula and T. philomelos confirmed that phanerozoites of P. matutinum pLINN1 develop in multiple organs [ 86 ], but tissue stages of pLINN1 were not yet studied in canaries. Additional experimental infections of canaries with pLINN1 could help confirm differences between P. giovannolai and P. matutinum pLINN1 regarding the location of tissue stage formation.…”
Section: Discussionmentioning
confidence: 99%
“…As Plasmodium infections (known to occur with lower average infection intensities than Haemoproteus parasites) and infections with both haemosporidian genera in particular led to such delays indicates that it is not infection intensity per se but rather a systemic effect of certain stages in the life cycle of parasites belonging to the genus Plasmodium . Studies on differential pathogenicity of haemosporidians revealed that specific lineages of Plasmodium parasites can be much more pathogenic than Haemoproteus infections, despite their relatively low parasitaemia (Himmel et al., 2020; Ilgūnas et al., 2016). Unfortunately, our sample size is insufficient for a lineage‐specific comparison.…”
Section: Discussionmentioning
confidence: 99%
“…For example, signals found in the lumen of blood vessels measuring up to the size of erythrocytes were regarded as blood stages, whereas signals located in other host cells and exceeding the size of erythrocytes were regarded as exoerythrocytic meronts. Detailed descriptions and examples on how CISH signals were distinguished can be found in [ 50 ]. In addition, corresponding HE-stained sections were checked to confirm presence or absence of exoerythrocytic stages.…”
Section: Methodsmentioning
confidence: 99%
“…Exploiting such archives of tissue samples, previous retrospective studies in Austria revealed an association of blackbird mortalities with the presence of widespread haemosporidian lineages [ 30 , 50 ]. Notably, severe parasite loads were linked to infections with Plasmodium matutinum LINN1, pointing towards its pathogenic role in these birds’ mortalities.…”
Section: Introductionmentioning
confidence: 99%